Security of Networks and Services in an All-Connected World: 11th IFIP WG 6.6 International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2017, Zurich, Switzerland, July 10-13, 2017, Proceedings - Tuncer, Daphne; Koch, Robert; Badonnel, Rémi; Stiller, Burkhard (Lecture Notes in Computer Science, 2017)
anomaly detection; artificial intelligence; cloud computing; data security; cyber crime; internet; network security; wireless; web